The demons of Leonard Cohen - Mus, Francis (Etudes canadiennes., 2020)
"Who speaks in Leonard Cohen's oeuvre? By identifying the many guises in which Cohen presents himself to his audience, Francis Mus seeks to formulate an answer to this question. The countless roles assumed by Cohen's persona are not some innocent game, but strategies in response to the sometimes conflicting demands of a 'life in art': they serve as masks that represent the performer's face and state of mind in a heightened yet detached way. In and around the artistic work, they are embodied in different guises or 'demons': image (the poser), artistry (the writer and singer), alienation (the stranger and the confidant), religion (the worshipper, prophet, or priest), and power (the powerful or powerless). Ultimately, Cohen's artistic practice can be read as an attempt at forging interpersonal contact. The wide international circulation of Cohen's work has resulted in a partial severing with the context of its creation. Much of it has filtered through the public image forged by the artist and his critics in concerts, interviews and reflective texts. Consequently, this monograph is less a biography than a reception study, supplemented with extensive archival research, unpublished documents, and interviews with colleagues and privileged witnesses. At the same time, this book sheds new light on the dynamic of a comprehensive oeuvre spanning a period of sixty years."--